Poor chemical and microbiological quality of the commercial milk thistle-based dietary supplements may account for their reported unsatisfactory and non-reproducible clinical outcomes - Fenclova, Marie; Novakova, Alena; Viktorova, Jitka; Jonatova, Petra; Dzuman, Zbynek; Ruml, Tomas; Kren, Vladimir; Hajslova, Jana; Vitek, Libor; Stranska-Zachariasova, Milena (Scientific reports, 2019)
Herbal-based dietary supplements have become increasingly popular. The extract from milk thistle (Silybum marianum), is often used for the treatment of liver diseases. However, serious concerns exist regarding the efficacy, composition, as well as the safety of these over-the-counter preparations. Therefore, the aim of the present study was to investigate the composition as well as chemical and biological safety of 26 milk thistle-based dietary supplements purchased from both the U.S. and Czech markets between 2016 and 2017. The study was focused on a determination of the composition of active ingredients, as well as analyses of possible contaminants including: mycotoxins, plant alkaloids, and pesticide residues, as well as the microbial purity. High-throughput analyses were performed using advanced U-HPLC-HRMS techniques. Large differences in the silymarin content were observed among individual milk thistle preparations, often in contrast with the information provided by the manufacturers. In addition, substantial inter-batch differences in silymarin content were also demonstrated. In all milk thistle preparations tested, large numbers and high concentrations of mycotoxins and several pesticides, as well as the substantial presence of microbiological contamination were detected, pointing to serious safety issues. In conclusion, our results strongly indicate the need for strict controls of the composition, chemical contaminants, as well as the microbiological purity of commercial milk thistle extracts used for the treatment of liver diseases. Poor definition of these preparations together with contamination by biologically active substances may not only account for the inconsistency of clinical observations, but also be responsible for possible herbal-based dietary supplements-induced liver injury.
Keywords: Mycotoxins; biologické přípravky; nemoci jater; Antioxidants; Biological Products; rostlinné extrakty; Dietary Supplements; Silybum marianum; lidé; Phytotherapy; potravní doplňky; mykotoxiny; ostropestřec mariánský; Liver Diseases; fytoterapie; silymarin; antioxidancia; Plant Extracts; Pesticides; pesticidy; Silymarin; Humans